2022
DOI: 10.1021/acsami.2c14740
|View full text |Cite
|
Sign up to set email alerts
|

Multielement Flame-Retardant System Constructed with Metal POSS–Organic Frameworks for Epoxy Resin

Abstract: The direct coordination between polyhedral oligomeric silsesquioxane (POSS) and Co forms an assembly of nanoparticles with low specific surface area and leads to a poor dispersion state in the epoxy resin matrix, resulting in unsatisfactory flame-retardant efficiency. Metal–organic frameworks (MOFs), for instance, ZIF-67, provide not only the cobalt element but also the porous framework that endows the nanocomposite of MOFs and POSS with high specific surface area and abundant Co sites in the silica skeleton. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…[ 38 ] It is well known that cobalt in a highly oxidized state has high catalytic activity, which is conducive to improving the compactness and strength of char residue. [ 39 ] In addition, the characteristic peak of Co 2 P 2 O 7 displayed in the XRD signal confirmed that Co‐PA participated in the charcoal formation process during combustion. The XPS results of the char residue are shown in Figure 5l,m, where Co, O, and C elements are present.…”
Section: Resultsmentioning
confidence: 81%
“…[ 38 ] It is well known that cobalt in a highly oxidized state has high catalytic activity, which is conducive to improving the compactness and strength of char residue. [ 39 ] In addition, the characteristic peak of Co 2 P 2 O 7 displayed in the XRD signal confirmed that Co‐PA participated in the charcoal formation process during combustion. The XPS results of the char residue are shown in Figure 5l,m, where Co, O, and C elements are present.…”
Section: Resultsmentioning
confidence: 81%
“…Figure 3 illustrates how FT‐IR was used to follow the changes in the chemical structure of MP. The FT‐IR spectrogram of the 3ONa‐POSS exhibits a distinct SiOSi antisymmetric stretching vibration peak at wave number 1133 cm −1 , 25 indicated that the product has a caged structure, and from the FT‐IR spectrogram of 3OH‐POSS, it can be seen that the product has a SiOH stretching vibration peak at 893 cm −1 , suggesting that the SiONa is acidified to SiOH 26 . Further the FT‐IR spectrogram demonstrates that γ‐aminopropylphenyl triethoxysilane reacted with 3OH‐POSS to form caged Ph 7 POSS‐NH 2 , and the disappearance of the stretching vibration peak of SiOH can be seen from the FT‐IR spectrum, while the stretching vibration peak of NH 2 appeared at 3304 cm −1 27 .…”
Section: Resultsmentioning
confidence: 98%
“…Polymers, including plastics, rubbers, and fibers, are manufactured in large quantities and are widely used in industry, civil, aerospace, furniture, clothing, automobiles, and many other fields. [1][2][3] Most polymeric materials are flammable and when they are ignited, lots of heat, soot, and toxic gases are released, which is harmful to the health of human beings and the environment. 4,5 To address these issues, in the past decades, efforts have been made to change their combustion performance via introducing additive flame retardants to suppress the flame propagation.…”
Section: Introductionmentioning
confidence: 99%
“…8 An alternative strategy is to explore intrinsic flame retarded polymers which are based on the monomers containing P, 5,9,10 N, [11][12][13] Si 14 or other flame retarded elements. 3,15 N-containing flame retarded components seem more promising, from the viewpoint of sustainability, since N-containing compounds can be sourced widely from biomass. N-containing components exhibit significant heat absorption during the combustion, thereby effectively cooling the polymer surface.…”
Section: Introductionmentioning
confidence: 99%